Active trachoma and associated risk factors among children in Baso Liben District of East Gojjam, Ethiopia - Ketema Kassahun; Tiruneh Moges; Woldeyohannes Desalegn; Muluye Dagnachew (BMC, 2012)
Abstract Background Trachoma is the leading cause of preventable blindness worldwide. It is common in areas where the people are socio-economically deprived. The aim of this study was to assess active trachoma and associated risk factors among children 1-9 years in East Gojjam. Methods Community-based cross-sectional study was conducted in Baso Liben District from February to April 2012. A two-stage random cluster-sampling technique was employed and all children 1-9 years old from each household were clinically assessed for trachoma based on simplified WHO 1983 classification. Data were collected by using semi-structured interview, pre-tested questionnaire and observation. The data were entered and analyzed using SPSS version 16 statistical package. Results From a total of 792 children screened for trachoma (of which 50.6% were girls), the overall prevalence of active trachoma was 24.1% consisting of only 17.2% [95% CI: 14.8, 20.1] TF and 6.8% TI. There were variations among children living in low land (29.3%) and in medium land (21.4%). In multivariate analysis, low monthly income (AOR = adjusted odds ratio) 2.98; 95% CI (confidence interval): 1.85-7.85), illiterate family (AOR = 5.18; 95% CI: 2.92-9.17); unclean face (AOR = 18.68; 95% CI: 1.98-175.55); access to water source (AOR = 2.01; 95% CI: 1.27-3.15); less than 20 liters of water use (AOR = 4.88; 95% CI: 1.51-15.78); not using soap for face washing (AOR = 5.84; 95% CI: 1.98-17.19); not using latrine frequently (AOR = 1.75; 95% CI: 0.01-0.42); density of flies (AOR = 3.77; 95% CI: 2.26-6.29); less knowledgeable family (AOR = 3.91; 95% CI: 2.40-6.38) and average monthly income (AOR = 2.98; 95% CI: 1.85-7.85) were found independently associated with trachoma. Conclusion Active trachoma is a major public problem among 1-9 years children and significantly associated with a number of risky factors. Improvement in awareness of facial hygiene, environmental conditions, mass antibiotic distribution and health education on trachoma transmission and prevention should be strengthened in the District.